Optical Distinction between "Slow" and "Fast" Translational Motion in Degenerate Molecular Shuttles. (1st February 2017) - Vukotic, V. Nicholas; Zhu, Kelong; Baggi, Giorgio; Loeb, Stephen J.
Abstract: A series of six [2]rotaxane molecular shuttles was designed which contain an axle with a benzo‐bis(imidazole) core (in either a neutral or dicationic form) and a single 24‐membered, crown ether wheel (24C6, B24C6, orDMB24C6 ), and the shuttling rates of the ring along the axle were determined. The charged versions showed much slower shuttling rates as a result of the increase in noncovalent interactions between the axle and wheel. The [2]rotaxane with aB24C6 wheel shows a difference in fluorescence between the charged and neutral species, while the [2]rotaxane with aDMB24C6 wheel exhibits a difference in color between the charged and neutral compounds. These changes in optical properties can be attributed to the structural differences in the co‐conformations of the [2]rotaxane as they adapt to the changes in acid/base chemistry. This allowed the relative rate of the translational motion of a molecular shuttle to be determined by observation of a simple optical probe.